Teaching Reform of Database Application based on Online and Offline Integrated Teaching - Pingshui, Wang (IJRDO- Journal of Educational Research, 2020)
Online and offline integrated teaching is a new teaching idea and teaching mode in recent years. The “Database Application” is a common basic course with rich theoretical and strongly practical in the higher school of finance and economics. However, due to the limited teaching hours and teaching environment, the traditional teaching mode has been unable to meet the need of practical teaching. Integrating the traditional face to face teaching and online learning (that is mixed online and offline teaching) can not only improve students' learning interest and teaching effect, but also students' autonomous learning ability.